Essential Functions of the Transcription Factor Npas4 in Neural Circuit Development, Plasticity, and Diseases - Fu, Jian; Guo, Ouyang; Zhen, Zhihang; Zhen, Junli (Frontiers in Neuroscience, 2020)
Signaling from the synapse to nucleus is mediated by the integration and propagation of both membrane potential changes (postsynaptic potentials) and intracellular second messenger cascades. The electrical propagation of postsynaptic potentials allows for rapid neural information processing, while propagating second messenger pathways link synaptic activity to the transcription of genes required for neuronal survival and adaptive changes (plasticity) underlying circuit formation and learning. The propagation of activity-induced calcium signals to the cell nucleus is a major synapse-to-nucleus communication pathway. Neuronal PAS domain protein 4 (Npas4) is a recently discovered calcium-dependent transcription factor that regulates the activation of genes involved in the homeostatic regulation of excitatory–inhibitory balance, which is critical for neural circuit formation, function, and ongoing plasticity, as well as for defense against diseases such as epilepsy. Here, we summarize recent findings on the neuroprotective functions of Npas4 and the potential of Npas4 as a therapeutic target for the treatment of acute and chronic diseases of the central nervous system.